Body temperature programmable elastic thermoset shape memory polymer with elastic transition part - Chan, Jun Wei (Nanyang Technological University, 2021)
A systematic approach to investigate the effects of elastic transition part in shape memory polymer. Elastic Polylactic acid and Thermoplastic polyurethane is selected to be the elastic transition part in shape memory polymer. Suitable fabrication procedures will be developed through experimentation. The SMP developed will go through differential scanning calorimetry and tensile test to evaluate its mechanical properties and to gather enough data to conduct other test such as shape fixity and recovery test and bonding test. These series of tests will help to evaluate its properties with relation to body temperature programming, stretchability and shape fixity and recovery. The SMP developed is designed to be highly stretchable and body temperature programmable without onset of failure through whitening effect.